Biocompatibility assessment of sub-5 nm silica-coated superparamagnetic iron oxide nanoparticles in human stem cells and in mice for potential application in nanomedicine. Issue 3 (2nd January 2020) - Ledda, Mario; Fioretti, Daniela; Lolli, Maria Grazia; Papi, Massimiliano; Di Gioia, Cira; Carletti, Raffaella; Ciasca, Gabriele; Foglia, Sabrina; Palmieri, Valentina; Marchese, Rodolfo; Grimaldi, Settimio; Rinaldi, Monica; et al.
Abstract : Ultrafine sub-5 SIO-Fl superparamagnetic nanoparticles evaluated in human stem cells and in mice as a novel promising biomaterial for application in nanomedicine. Abstract : Ultrasmall superparamagnetic iron oxide nanoparticles with a size <5 nm are emerging nanomaterials for their excellent biocompatibility, chemical stability, and tunable surface modifications. The applications explored include dual-modal or multi-modal imaging, drug delivery, theranostics and, more recently, magnetic resonance angiography. Good biocompatibility and biosafety are regarded as the preliminary requirements for their biomedical applications and further exploration in this field is still required. We previously synthesized and characterized ultrafine (average core size of 3 nm) silica-coated superparamagnetic iron oxide fluorescent nanoparticles, named sub-5 SIO-Fl, uniform in size, shape, chemical properties and composition. The cellular uptake and in vitro biocompatibility of the as-synthesized nanoparticles were demonstrated in a human colon cancer cellular model. Here, we investigated the biocompatibility of sub-5 SIO-Fl nanoparticles in human Amniotic Mesenchymal Stromal/Stem Cells (hAMSCs). Kinetic analysis of cellular uptake showed a quick nanoparticle internalization in the first hour, increasing over time and after long exposure (48 h), the uptake rate gradually slowed down. We demonstrated that after internalization, sub-5 SIO-Fl nanoparticles neither affect hAMSC growth, viability, morphology, cytoskeletal organization, cell cycle progression, immunophenotype, and the expression of pro-angiogenic and immunoregulatory paracrine factors nor the osteogenic and myogenic differentiation markers. Furthermore, sub-5 SIO-Fl nanoparticles were intravenously injected into mice to investigate the in vivo biodistribution and toxicity profile for a time period of 7 weeks. Our findings showed an immediate transient accumulation of nanoparticles in the kidney, followed by the liver and lungs, where iron contents increased over a 7-week period. Histopathology, hematology, serum pro-inflammatory response, body weight and mortality studies demonstrated a short- and long-term biocompatibility and biosafety profile with no apparent acute and chronic toxicity caused by these nanoparticles in mice. Overall, these results suggest the feasibility of using sub-5 SIO-Fl nanoparticles as a promising agent for stem cell magnetic targeting as well as for diagnostic and therapeutic applications in oncology.